2013
DOI: 10.1142/s1088424613500016
|View full text |Cite
|
Sign up to set email alerts
|

Axial coordination of zinc and silicon phthalocyanines to silver and gold nanoparticles: an investigation of their photophysicochemical and antimicrobial behavior

Abstract: This work reports on the axial coordination of zinc phthalocyanine and bis-(1,6-hexanedithiol) silicon phthalocyanine to silver and gold nanoparticles. Red shifting of absorption spectra of the phthalocyanine complexes was observed after conjugation with the nanoparticles. An improvement in the photophysicochemical behavior and antimicrobial activity was achieved in the presence of metal nanoparticles for both complexes. A decrease in triplet lifetimes was observed for all the phthalocyanine metal nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…Both systems exhibit a strong surface plasmon resonance in the visible range of the electromagnetic spectrum. Several papers report on zinc(II) phthalocyanines derivatives substituted mainly by thiol-groups and then anchored to AuNPs (sizes of particles 5 nm) [32,33,[37][38][39][40][41][42]. These conjugates have gained growing interest for drug delivery applications and for photodynamic therapy (PDT) due to the colloidal character of AuNPs [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both systems exhibit a strong surface plasmon resonance in the visible range of the electromagnetic spectrum. Several papers report on zinc(II) phthalocyanines derivatives substituted mainly by thiol-groups and then anchored to AuNPs (sizes of particles 5 nm) [32,33,[37][38][39][40][41][42]. These conjugates have gained growing interest for drug delivery applications and for photodynamic therapy (PDT) due to the colloidal character of AuNPs [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…DPBF is a chemical quencher for singlet oxygen and reacts selectively and quantitatively via an endoperoxide to 1,2-dibenzoylbenzene ( Figure 4a). DPBF is mostly used as standard method for the calculation of singlet oxygen quantum yields obtained by photocatalysts [31][32][33][34][35][36]. The degradation of DPBF can be followed by the decrease of the absorption at λ = 415 nm ( Figure S7-S9).…”
Section: Investigation Of Photocatalytic Dpbf Oxidationsmentioning
confidence: 99%
“…Thus, it is important to find a photocatalyst that can degrade this dye into biodegradable species as is the aim of the work. Conjugating silver nanoparticles to Pcs has been reported to enhance the photophysicochemical properties of the later [25,26], this has been attributed to the heavy atom effect of silver. In addition, reports have shown that coupling metal nanoparticles such as of silver or gold to a photocatalyst may induce what is known as plasmonic photocatalysis [27][28][29][30], depending on the excitation wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…1,[22][23][24][25] The introduction of light absorbing chromophores is thereby of great interest, as interactions with the surface plasmons of gold nanostructures were shown to have an increasing effect onto the photocatalytic activity of such hybrid materials. [26][27][28][29][30] Recent studies revealed an increase in singlet oxygen formation by nearly an order of magnitude when a zinc(II) phthalocyanine derivative was immobilized onto a npAu as additional chromophore, that can be used for example for the photooxidation of citronellol, a reaction that is also of industrial relevance. 24 A severe drawback in heterogeneous photocatalysis with porous catalysts is the limited penetration depth of visible light in such materials.…”
Section: Introductionmentioning
confidence: 99%